Attentional biases towards emotional scenes in autism spectrum condition: An eye-tracking study. (January 2022) - Sahuquillo-Leal, Rosa; Navalón, Pablo; Moreno-Giménez, Alba; Almansa, Belén; Vento, Máximo; García-Blanco, Ana
Highlights: This study examines the attentional biases in autism with a highly ecological setting. Threatening scenes captured early attention of individuals with autism. A late avoidance of threatening scenes was identified in individuals with autism. Attentional problems and somatic complaints were related to the threat-related bias. The findings suggest a hypersensitivity to threatening information in individuals with autism. Abstract: Background: Different attentional processing of emotional information may underlie social impairments in Autism Spectrum Condition (ASC). It has been hypothesized that individuals with ASC show hypersensitivity to threat, which may be related to an avoidance behaviour. However, research on the attentional processing of emotional information in autism is inconclusive. Aim: To examine the attentional processing biases of 27 children with ASC and 25 typically developed (TD) participants. Methods and procedures: The initial orienting of attention, the attentional engagement, and the attentional maintenance to complex emotional scenes in competition (happy, neutral, threatening, sad) were assessed in a 20-second eye-tracking based free-viewing task. Outcomes and results: i) children with ASC showed an initial orienting bias towards threatening stimuli; ii) TD children demonstrated an attentional engagement and maintenance bias towards threat, while children with ASC did not; and iii) in children with ASC, attentional problems and somatic complaints were associated with higher initial orienting and with higher attentional maintenance towards threat, respectively. Conclusions and implications: These results suggest that a perceived threat induces an early overwhelming response in autism, giving rise to an avoidance behaviour. The findings endorse affective information processing theories and shed light on the mechanisms underlying social disturbances in ASC.